Exploring Students’ Experiences of Weekly Vlogging in Indonesian Language Learning at Madrasah Aliyah - Muhammad Fahrurrozi; Safrina Rati (STIT Buntet Pesantren Cirebon, 2026)
Integrating weekly vlogging into Bahasa Indonesia lessons offers a promising yet demanding approach at a time when digital literacy is becoming central to classroom learning. This study examines how eleventh-grade students at a Madrasah Aliyah (Islamic senior high school) in Cirebon reflected on weekly vlog assignments used to build their Indonesian-language speaking skills. It addresses the challenges students faced and the pedagogical implications of vlog-based tasks in secondary madrasah education. An explanatory sequential mixed-methods design was applied to collect data from 32 eleventh-grade students. Data were gathered through a structured questionnaire and in-depth interviews with three students representing different performance levels. Quantitative results showed that affective, technical, linguistic, and time-management issues were rated as moderately to fairly challenging. Students reported clear benefits, including greater confidence, improved formal Indonesian speaking skills, and stronger motivation. Qualitative findings confirmed these results, revealing increased autonomy, self-reflection, and classroom engagement. The study concludes that, despite its challenges, weekly vlogging is a meaningful strategy for developing Bahasa Indonesia speaking competence in madrasah settings.